Immunochromatographic Test and ELISA for Detection of Rotavirus in Fecal Sample : A Comparative Study (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2020)
Background: Rotavirus is a common cause of diarrhea in children. Early diagnosis of rotavirus infection helps to determine appropriate treatment thus preventing unnecessary use of antibiotics and minimizes its spread. Rapid test using lateral flow immunochromatography is a good alternative to Enzyme Linked Immunosorbent Assay (ELISA) with good sensitivity. This study was undertaken to compare Immunochromatographic Test (ICT) with ELISA for detection of rotavirus antigen in stool sample.Materials and methods: Ninety stool samples from hospitalized children less than two years of age with symptoms of acute gastroenteritis were tested by both ICT and ELISA. Sensitivity and specificity was compared.Results: Out of 90 samples 63.3% were positive for rotavirus antigen by ELISA and 51% were positive by ICT. Sensitivity and specificity of ICT was determined considering ELISA as a gold standard. Sensitivity of ICT was 80.7% whereas specificity was 100%.Conclusion: Rotavirus gastroenteritis cases can be diagnosed by rapid test (Immunochromatography) with high sensitivity and specificityChatt Maa Shi Hosp Med Coll J; Vol.18 (2); July 2019; Page 7-11